KINETIC AND EQUILIBRIUM ISOTHERM OF PESTICIDES (ATRAZINE) ADSORPTION UNTO ACTIVATED CARBON OF CALABASH (LAGENARIA SICERARIA) - Chukwudi-Madu, E,; Agboeze, Emmanuel,; Chime, C.C,; Nwadiogbu, J. O,; Ajah, N, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The adsorption of pesticides (Atrazine) from water onto activated carbon prepared from calabash was investigated. The kinetic and equilibrium study was carried out, and data obtained showed that time duration, the concentration of the solution, the dosage of activated carbon and the pH of the solution greatly influenced the adsorption process. The adsorption kinetic study of the pesticide was done using various models. The result best fits pseudo-second-order using the coefficient regression value (0.9922) and intraparticle diffusion. Equilibrium isotherm data were analysed using the Langmuir isotherm model and Freundlich isotherm model. The result of the regression value provided Freundlich isotherm as the best fit to the experimental data, indicating the presence of heterogeneous layer sorption from the regression value of 0.7294. This study suggested that the activated carbon of calabash as a low-cost material is suitable for the adsorption of pesticides from water. Hence it could be applied as a cheap and effective material in removing pesticides in water bodies or industrial waste before disposal.